Marketing Innovation Through Integrated Social Media in Small Bussiness Wood Artists by Karya Langit Mangunan Bantul - Mulyanto, Indro Herry; Prabowo, Agung (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to design a way of marketing wooden handicraft products in the ’Karya Langit’ Craftsmen Group. Product marketing originally relied on word of mouth (WOM). In this research, marketing is done using integrated social media. Marketing through integrated social media is assumed to expand the market and allow craftsmen to communicate with consumers without the constraints of distance or pandemic situations. The method used by the researcher is a qualitative method that is exploratory in nature. Exploration here is in the context of extracting material to create social media content, both images, and product creation processes. The steps taken are (1) Exploring material that will be used as content on social media; (2) Processing the material to be used as content on social media; (3) Creating promotional applications on social media; (4) Training on content creation and uploading to social media. The results showed that ’Karya Langit’ woodcraft products have strength in the types of kitchen utensils and health accessories. As for the type of decoration they bring from outside. It still takes time to educate the craftsmen to promote on social media because the process, according to them, is not instant.